2003
DOI: 10.1079/nrr200362
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in physiological and pathological significance of NAD+metabolites: roles of poly(ADP-ribose) and cyclic ADP-ribose in insulin secretion and diabetogenesis

Abstract: Poly(ADP-ribose) synthetase/polymerase (PARP) activation causes NAD + depletion in pancreatic β-cells, which results in necrotic cell death. On the other hand, ADP-ribosyl cyclase/cyclic ADPribose hydrolase (CD38) synthesizes cyclic ADP-ribose from NAD + , which acts as a second messenger, mobilizing intracellular Ca 2+ for insulin secretion in response to glucose in β-cells. PARP also acts as a regenerating gene (Reg) transcription factor to induce β-cell regeneration. This provides the new concept that NAD +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 130 publications
2
7
0
Order By: Relevance
“…This result might be explained also referring to our previous studies conducted on diabetic and hyperlipidemic rabbits (Ragazzi et al, 2002), showing that in these pathological conditions, in comparison to normometabolic controls, the degradation of tryptophan is selectively affected mainly at the level of 3-hydroxyanthranilate 3,4-dioxygenase, which is reduced in kidneys, and at the level of aminocarboxymuconate-semialdehyde decarboxylase whose activity is increased in kidneys and liver. The slight increase of the activity of 3-hydroxyanthranilate 3,4-dioxygenase induced by cloricromene in the liver, observed in this study, both in diabetic/hyperlipidemic rabbits and controls, may suggest a protective event through the activation of the metabolic conversion of tryptophan toward NAD + synthesis, which has been indicated as a pivotal keypoint linked to diabetic condition (Okamoto, 2003). However, the opposite effect induced by cloricromene in the kidneys of control animals may suggest complex enzymatic adjustment within the last steps of the kynurenine pathway.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…This result might be explained also referring to our previous studies conducted on diabetic and hyperlipidemic rabbits (Ragazzi et al, 2002), showing that in these pathological conditions, in comparison to normometabolic controls, the degradation of tryptophan is selectively affected mainly at the level of 3-hydroxyanthranilate 3,4-dioxygenase, which is reduced in kidneys, and at the level of aminocarboxymuconate-semialdehyde decarboxylase whose activity is increased in kidneys and liver. The slight increase of the activity of 3-hydroxyanthranilate 3,4-dioxygenase induced by cloricromene in the liver, observed in this study, both in diabetic/hyperlipidemic rabbits and controls, may suggest a protective event through the activation of the metabolic conversion of tryptophan toward NAD + synthesis, which has been indicated as a pivotal keypoint linked to diabetic condition (Okamoto, 2003). However, the opposite effect induced by cloricromene in the kidneys of control animals may suggest complex enzymatic adjustment within the last steps of the kynurenine pathway.…”
Section: Discussionsupporting
confidence: 47%
“…Since alterations of tryptophan metabolism have been reported in diabetes and atherosclerosis (Kotake and Tani, 1953;Rosen et al, 1955;Wiseman et al, 1958;Oka and Leppänen, 1963;Ragazzi et al, 2002;Okamoto, 2003), it was thought of interest to investigate any role of cloricromene through the influence on the oxidative metabolism of the amino acid. In diabetic animals the shift of tryptophan metabolism to xanthurenic acid (Kotake and Tani, 1953) and the reduction of kidney 3-hydroxyanthranilate 3,4-dioxygenase activity (Ragazzi et al, 2002) have been observed (Scheme 1), leading to impairment of NAD + synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations